Price response to consumer attention during major animal epidemics in developing markets: perspectives from the influence of information and emotion contagion - Li, Xia; Ji, Jing (Frontiers in Sustainable Food Systems, 2025)
Major animal epidemics can significantly disrupt the pork market. Understanding how consumer network attention, triggered by these epidemics, impacts pork price fluctuations is of great significance for maintaining market stability and ensuring food security. This study focuses on exploring this complex relationship, with a particular emphasis on the roles of information dissemination and emotion transmission. Taking African Swine Fever (ASF) as a case study, monthly provincial panel data from June 2021 to November 2022 were collected. Web scraping techniques and social network analysis were employed. Weibo user repost and emotion transmission networks were constructed, integrating social network structures into the analytical framework to comprehensively analyze the problem. The study reveals several important findings. Firstly, consumer network attention significantly intensifies pork price volatility during major epidemics, and there is notable heterogeneity across different information environments. Secondly, both information dissemination and emotion transmission play moderating roles. Specifically, the media information index negatively moderates the relationship between consumer attention and pork price fluctuations. The betweenness centrality of the Weibo repost network also has a negative moderating effect, indicating that “opinion leaders” on social media can mitigate the impact of consumer attention on price fluctuations through selective information dissemination. In contrast, the closeness centrality of the emotion transmission network has a positive moderating effect, highlighting the amplifying effect of rapid emotion propagation on market reactions. This research highlights the economic implications of the relationship between consumer network attention, information dissemination, emotion transmission, and pork price fluctuations during food safety incidents. It emphasizes the importance of understanding these dynamics for maintaining food market stability.